PROTACs targeting androgen receptor signaling: Potential therapeutic agents for castration-resistant prostate cancer - Yulu Zhang; Annan Ming; Junyan Wang; Wenmin Chen; Zhiqing Fang (Elsevier, 2024)
After the initial androgen deprivation therapy (ADT), part of the prostate cancer may continuously deteriorate into castration-resistant prostate cancer (CRPC). The majority of patients suffer from the localized illness at primary diagnosis that could rapidly assault other organs. This disease stage is referred as metastatic castration-resistant prostate cancer (mCRPC). Surgery and radiation are still the treatment of CRPC, but have some adverse effects such as urinary symptoms and sexual dysfunction. Hormonal castration therapy interfering androgen receptor (AR) signaling pathway is indispensable for most advanced prostate cancer patients, and the first- and second-generation of novel AR inhibitors could effectively cure hormone sensitive prostate cancer (HSPC). However, the resistance to these chemical agents is inevitable, so many of patients may experience relapses. The resistance to AR inhibitor mainly involves AR mutation, splice variant formation and amplification, which indicates the important role in CRPC. Proteolysis-targeting chimera (PROTAC), a potent technique to degrade targeted protein, has recently undergone extensive development as a biological tool and therapeutic drug. This technique has the potential to become the next generation of antitumor therapeutics as it could overcome the shortcomings of conventional small molecule inhibitors. In this review, we summarize the molecular mechanisms on PROTACs targeting AR signaling for CRPC, hoping to provide insights into drug development and clinical medication.